OPTIMASI PARAMETER PEMESINAN WIRE ELECTRIC DISCHARGE MACHINING BAJA PERKAKAS SKD 11 MENGGUNAKAN METODE TAGUCHI - Setiawan Okik Aris; Djumhariyanto Dwi; Mulyadi Santoso (ROTOR, 2018)
EDM wire is one of the non-conventional machinings that is currently widely used in the manufacturing industry because it can process workpieces with hard material and also produces excellent dimensional accuracy. This research was carried out with variable current, voltage and wire speed processes. While the response variable is the material removal rate and cutting width (kerf), this study aims to determine the effect of each factor on each response as well as on the combined response and to find the right combination of parameters to produce optimal response values. The results of the study stated that the current strong factor contributed 89.84% and the wire speed factor was 8.26% against the cutting width response (kerf). The current strong element contributes 87.88% to the material removal rate response. As for the combined response, the influential factor was wire speed with a contribution of 92.79%. The optimal combination of parameters in the combined response is 7 amperes, 5 volts and 10 m / s wire speed. The conclusion of this study informs that the smaller the current strength, the better the value of the cutting width, while the more significant the current force will result in a higher removal rate material. The factor that influences the combined response is wire speed, where the increase in the value of the wire speed increases the amount of the Gray Relational Grade from the combined response. Keywords: Wire EDM, SKD 11 Steel, Taguchi, Optimization